Middle to Late Devonian–Carboniferous collapse basins on the Finnmark Platform and in the southwesternmost Nordkapp basin, SW Barents Sea - Koehl, Jean-Baptiste; Bergh, Steffen G; Henningsen, Tormod; Faleide, Jan Inge (Solid Earth, 2018)
Source at https://doi.org/10.5194/se-9-341-2018. The SW Barents Sea margin experienced a pulse of extensional deformation in the Middle–Late Devonian through the Carboniferous, after the Caledonian Orogeny terminated. These events marked the initial stages of formation of major offshore basins such as the Hammerfest and Nordkapp basins. We mapped and analyzed three major fault complexes, (i) the Måsøy Fault Complex, (ii) the Rolvsøya fault, and (iii) the Troms–Finnmark Fault Complex. We discuss the formation of the Måsøy Fault Complex as a possible extensional splay of an overall NE–SW-trending, NW-dipping, basement-seated Caledonian shear zone, the Sørøya–Ingøya shear zone, which was partly inverted during the collapse of the Caledonides and accommodated top–NW normal displacement in Middle to Late Devonian–Carboniferous times. The Troms–Finnmark Fault Complex displays a zigzag-shaped pattern of NNE–SSW- and ENE–WSW-trending extensional faults before it terminates to the north as a WNW–ESE-trending, NE-dipping normal fault that separates the southwesternmost Nordkapp basin in the northeast from the western Finnmark Platform and the Gjesvær Low in the southwest. The WNW–ESE-trending, margin-oblique segment of the Troms–Finnmark Fault Complex is considered to represent the offshore prolongation of a major Neoproterozoic fault complex, the Trollfjorden–Komagelva Fault Zone, which is made of WNW–ESE-trending, subvertical faults that crop out on the island of Magerøya in NW Finnmark. Our results suggest that the Trollfjorden–Komagelva Fault Zone dies out to the northwest before reaching the western Finnmark Platform. We propose an alternative model for the origin of the WNW–ESE-trending segment of the Troms–Finnmark Fault Complex as a possible hard-linked, accommodation cross fault that developed along the Sørøy–Ingøya shear zone. This brittle fault decoupled the western Finnmark Platform from the southwesternmost Nordkapp basin and merged with the Måsøy Fault Complex in Carboniferous times. Seismic data over the ...